Elderly with knee osteoarthritis should perform nutritional assessment: integrative literature review - Souza,Isabelle Ferreira da Silva (2017)
ABSTRACT To review scientific literature to assess nutritional status of elderly patients with osteoarthritis in the last 16 years. This is an integrative literature review that included articles published in national and international journals indexed in PubMed, SciELO and BIREME. We selected 14 articles, and English language was predominant. The year of publication of articles ranged from 2006 to 2016, and most of papers were cross-sectional studies. To gather papers and for posterior evaluate, we used a validated data collection instrument and the included studies were critical analyzed by reading, gathering and analysis of articles. Studies suggested that there is a positive correlation between obesity and knee osteoarthritis. Obesity is one of the most important modifiable factors in worsening of osteoarthritis symptoms.